PENGGUNAAN MEDIA FLIPBOOK BERGAMBAR DALAM MEMBACA PERMULAAN PADA SISWA KELAS III SDN KELAYAN SELATAN 8 BANJARMASIN - Dwi Nurdhini; Noor Indah Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Beginning reading is the initial stage for children in elementary school so that students can learn fluently. This research was motivated by third-grade students at SDN Kelayan Selatan 8 Banjarmasin who still experience difficulties in beginning reading, such as difficulty combining letters into syllables, reading letter-by-letter, and distinguishing letters with similar shapes such as “b” and “d”. One cause is the lack of interesting learning media in the teaching and learning process. This research aims to describe the use of illustrated flipbook media in beginning reading and students’ experiences of using it. This research uses a qualitative approach with a descriptive method. Data collection was carried out by triangulation through observation, in-depth interviews, and documentation. The primary data sources are the homeroom teacher and third-grade students of SDN Kelayan Selatan 8 Banjarmasin. Data analysis includes data reduction, data presentation, and drawing conclusions. The results show that the illustrated flipbook media used is a non-digital visual media in the form of an A5-sized desk calendar developed using Canva. The media has two vertical panels: the left panel contains concrete picture illustrations, and the right panel contains syllable spelling text and complete sentences. The media is used through four systematic stages: picture recognition, spelling syllables, reading complete sentences, and evaluation by matching pictures and text. Students’ learning experience shows a positive change, namely increased enthusiasm, motivation, focus, and courage in trying to read. The illustrated flipbook media proved most effective when used in a small group or individual learning context.